Fellowship Training in Nepal: Current Prospects - Neupane, Harish Chandra; Shrestha, Niki; Shrestha, Bishow Kumar (Journal of Nepal Health Research Council, 2018)
The need of subspecialty training has been acutely felt in Nepal now with the rapid advancement in the field of medical sciences, the changing burden of diseases, the acute shortage of highly specialized health professionals, the evolving concept of learning and medical education and the ever-increasing focus on right and safety of patients.Fellowship Training is obtained in a specific specialty or subspecialty. Fully academic 3-year Fellowship programsin Pulmonary and Critical Care Medicine, Hepatopancreatobiliary Surgery and Cardiologyhavebeen initiated for certification of the training for the first time in Nepal at Chitwan Medical College (CMC) and all three are recognized by the Nepal Medical Council.The three Fellowship training programs, run in affiliation with Lincoln University, at the CMC have all the training criteria of DM/MCh included along with extra requirement of one more paper publication and the trainees are paid adequate stipend without any tuition fee or bond. The high volume of cases and procedures in CMC, exposes the FCMC Fellows to an increased chance of appropriate skill development along with appropriate postings in various other institutions for adequate experience of hands on training.Fellowship programs are the cornerstone of providing super specialized patient care.The need today is to focus on the basic training concepts and criteria, rather than on various names like diploma, MD, MS, DM/MCh of training.Nepal should focus onthe prerequisites, infrastructure and human resource for expanding the quality Fellowship trainingprograms in the country and thereby enhancing the standard of patient care.